Law no. 17 of the year 1999 promulgating the trade law. (2025)
First: Law No. 17/1999 Promulgating The Trade Law. -- Part I: Trade in general. - Chapter: 1 Commercial activities. - Chapter: 2 The trader.- Chapter: 3 Commercial books. -- Chapter: 4 Commercial register - Chapter 5 Trading shop. - Chapter: 6 Stock Exchange. -- Part - II: Commercial obligations and contracts (General Provisions) - Chapter: 1 Transfer of technology. - Chapter 2 Commercial sale. - Chapter :3 Commercial pawn. - Chapter:4 Depositing in general warehouses.- Chapter: 5 Commercial agency - Chapter: 6 Brokerage. - Chapter7 Transport (General Provisions) -- Part II: Banking transactions. -- Part - IV Commercial paper.- Chapter 1 Drafts. - Chapter:2 Promissory note. - Chapter: 3 The check. - Chapter:4 Common provisions. -- Part V: Bankruptcy and composition. - Chapter: I Declaration of bankruptcy - Chapter 2 Persons managıing the bankruptcy. - Chapter 3 Bankruptcy effects. - Chapter 4 Management of bankruptcy. - Chapter: 5 End of bankruptcy - Chapter 6 Curtailed proceedings. - Chapter: 7 Bankruptcy of companies. - Chapter: 8 Commercial rehabilitation. - Chapter: 9 Composition bankruptcy. - Chapter: 10 Bankruptcy crimes and composition bankruptcy. -- Second: Chapter one of part two of Trade Law issued on 13/11/1883 on companies -- List of the Egyptian Economic Laws Available In English